2012
DOI: 10.1128/aem.01372-12
|View full text |Cite
|
Sign up to set email alerts
|

Testing Potential Effects of Maize Expressing the Bacillus thuringiensis Cry1Ab Endotoxin (Bt Maize) on Mycorrhizal Fungal Communities via DNA- and RNA-Based Pyrosequencing and Molecular Fingerprinting

Abstract: eThe cultivation of genetically modified (GM) crops has increased significantly over the last decades. However, concerns have been raised that some GM traits may negatively affect beneficial soil biota, such as arbuscular mycorrhizal fungi (AMF), potentially leading to alterations in soil functioning. Here, we test two maize varieties expressing the Bacillus thuringiensis Cry1Ab endotoxin (Bt maize) for their effects on soil AM fungal communities. We target both fungal DNA and RNA, which is new for AM fungi, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 63 publications
(54 reference statements)
2
41
0
Order By: Relevance
“…De Vaufleury et al (2007) found no difference in mycorrhizal colonisation between Bt (MEB307 expressing Cry1Ab toxin) and non Bt maize lines. Verbruggen et al (2012) tested two maize cultivars (Cry1Ab) for their effects on soil AM fungal communities and the main conclusion of the experiment was that no consistent difference was detected between AM fungal communities associated with GM and non-GM plants. These results are in contrast with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…De Vaufleury et al (2007) found no difference in mycorrhizal colonisation between Bt (MEB307 expressing Cry1Ab toxin) and non Bt maize lines. Verbruggen et al (2012) tested two maize cultivars (Cry1Ab) for their effects on soil AM fungal communities and the main conclusion of the experiment was that no consistent difference was detected between AM fungal communities associated with GM and non-GM plants. These results are in contrast with our findings.…”
Section: Resultsmentioning
confidence: 99%
“…biotic or abiotic. Starting from the available literature we proposed and assessed the potential risk related to thirteen possible stresses: (1) climate change (global warming) (Van der Putten, 2012), (2) land use change (Spurgeon et al, 2013), (3) habitat fragmentation (Halme et al, 2013), (4) intensive human exploitation (Tsiafouli et al, 2015), (5) soil organic matter decline (Heenan et al, 1995), (6) industrial pollution (Hafez and Elbestawy, 2009), (7) nuclear pollution (radioactivity) (Brodie et al, 2006), (8) soil compaction (Whalley et al, 1995), (9) soil erosion (Pimentel et al, 1995), (10) soil sealing (Setälä et al, 2014), (11) soil salinization (Sardinha et al, 2003), (12) use of genetically modified organisms (GMOs) in agriculture (Verbruggen et al, 2012), and (13) introduction and diffusion of invasive species (Kourtev et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…intensive human exploitation or soil pollution) on specific groups of soil organisms (e.g. bacteria or earthworms) (Verbruggen et al, 2012). Therefore, we can assume that the scientific community has an appropriate level of knowledge on this topic and, therefore, a knowledge-based assessment of potential risk is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The EFSA GMO Panel considers that conclusions about potential adverse effects of maize MON 810 and the Cry1Ab protein it expresses on non-target organisms and the ecosystem services they provide and/or routes of exposure to plant-produced Bt-toxins can be drawn from the studies by Peterson et al and Verbruggen et al (2012), and that the conclusions reached by the authors are supported by the data.…”
Section: Resultsmentioning
confidence: 99%